Nueva forma de Heliconius cydno (Lepidoptera: Heliconidae) en el río Sarapiquí, Costa Rica - Posla F., Mario (1993)
Only two forms of the butterfly Heliconius cydno were known from Costa Rica, cydno galanthus and cydno chioneus. A new form, found in !he Caribbean slope (Near Río Sarapiquí, limón Prov., 600 m elevation) is illustrated in color and described.